PENGARUH OCCUPATIONAL SELF EFFICACY TERHADAP WORK ENGAGEMENT YANG DIMEDIASI OLEH HUMAN RESOURCE DEVELOPMENT CLIMATE DI PT OLYMPIC BANGUN PERSADA - Adelina Ariani; Yohanes Arianto Nugroho (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The purpose of this research is to inspect the impact Occupational Self Efficacy on Work Engagement with the role of Human Resource Development Climate as mediating variable. This research was conducted at the Head Office of PT OLYMPIC BANGUN PERSADA involving several employee within the organization. The authors distribute questionnaires consisting of 15 questions about Occupational Self Efficacy, 15 questions about Work Engagement, 15 questions about Human Resources Development Climate to 100 respondents at PT OLYMPIC BANGUN PERSADA. The data were processed with SPSSv23 and macro Hayes v3. The findings showed significant relationship was found between all variables in the study. All the study hypotheses were supported. Human Resource Development Climate was found to partially mediate the relationship between Occupational Self-Efficacy and Work Engagement. The findings on respondents showed that Human Resource Development Climate has a role as complementary mediation.